Grinding Force Model of the Grinding Helical Gear by Using Forming Method - Wang Huiliang; Xiong Yuquan; He Guangqiang (Jixie chuandong)
Based on the geometric principles of the 5-axis CNC forming grinding and machine kinematics principle,the line speed of wheel at any points is deduced.According to the traditional plane grinding force model,these relationships are used that molding grinding involute length is approximately equal to the width of the plane grinding wheel,the diameter of wheel in contact with the tooth surface is approximately equal to the diameter of the plane grinding wheel,the wheel feed amount is approximately equal to the grinding surface grinding depth.So the grinding force model are established,the grinding force simulation program is composed and the experimental schemes are design,lastly this grinding force formula can guarantee a certain precision.